Fibular grafts in global reconstructive surgery: a bibliometric analysis - Zhang, Zhi; Li, Yuezhan; Cheng, Lin; Deng, Ying; Cai, Yan (Frontiers in Surgery, 2024)
BackgroundOver the past few decades, fibular grafts have been widely utilized across 86 countries and regions globally for surgical reconstruction of various anatomical sites, including the mandible, upper extremities, lower extremities, spine, and in phalloplasty procedures. The present study aims to systematically investigate the developmental trajectory of fibular graft and identify research priorities for surgeons.MethodsA bibliometric analysis was conducted by searching the Web of Science Core Collection on April 12, 2024, for articles published between 2004 and 2023 on fibular grafting, using the query TS = (“graft” OR “transfer” OR “flap”) AND TS = (“fibular”). We included full-text English articles and reviews, and exclude documents that were not related to fibular grafting or were non-research-oriented publications. GraphPad Prism, CiteSpace, and VOSviewer analyzed publication trends and co-citation networks, providing insights into fibular grafting research.ResultsA total of 2,884 fibular graft publications were analyzed. Out of 86 countries/regions, the United States and China stood out as the main contributors in terms of publication volume, while England had the highest citation rate per publication. The journals with the most publications and citations were The Journal of Craniofacial Surgery and Plastic and Reconstructive Surgery, respectively. Mark K. Wax had the most publications, while Hidalgo DA had the highest co-citation count. The most frequently occurring keywords were “reconstruction” and “mandibular reconstruction.” Co-citation reference clustering revealed a growing preference for vascularized fibular grafts over non-vascularized alternatives. The top 10 co-cited references were exclusively focused on mandibular reconstruction. Keyword bursts analysis showed that over the initial 20-year period, identified keywords fall into three main themes: graft design (e.g., osteoseptocutaneous flap, perforator flap), reconstruction areas (e.g., maxilla, extremity, ankle, spine and phalloplasty), and defect causes (e.g., pseudarthrosis, sarcoma, bone tumor). In particular, fibular grafts in phalloplasty represent an emerging trend among various anatomical reconstruction sites. In the last 5 years, there has been a notable rise in interest in 3D planning, virtual surgical planning, augmented reality, and reconstruction accuracy.ConclusionThe findings offer an in-depth overview of the landscape of fibular graft research, highlighting key contributors and emerging trends.